Agile Game Development : Build, Play, Repeat - Keith, Clinton (Addison-Wesley Professional, 2020)
In Agile Game Development, Clinton Keith offered game development team members the first complete blueprint for leveraging the power of Scrum and Agile methods to deliver games more efficiently, rapidly, and cost-effectively; create games that offer more entertainment value; and make life more fulfilling for every development team member. Now, reflecting his unsurpassed experience helping more than 150 game development studios succeed, Keith has thoroughly revamped his classic guide for today's radically transformed industry. The only Certified Scrum Trainer to help build 20 AAA-level games, Keith is singularly well-placed to help game developers solve the problems they actually face. In this edition, he: Addresses the modern challenges of mobile, free-to-play, and Massively Agile games Adds a completely new section on large-scale Agile game development, and new chapters on managing the first release, forming and leading Agile teams, game pipelines, and more Presents many new date stories about the experiences of actual game development teams, with actionable takeaways Illuminates advanced Agile projects through new "Things to Try" sidebars Covers Kanban and other Agile methodologies as well as Scrum Around the world, thousands of professional game developers have already used Agile Game Development to dramatically improve their effectiveness - and enjoy their work more. This 2nd Edition offers today's professionals even more value - no matter what types of games they're developing, what development roles they play, or what environments they're working in